2008
DOI: 10.1128/jcm.00192-08
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Broadly Reactive Reverse Transcription-PCR Assays To Detect Novel Paramyxoviruses

Abstract: We have developed a set of reverse transcription-PCR assays for the detection and identification of known and novel paramyxoviruses in clinical specimens. Primers were designed from the conserved motifs of the polymerase pol gene sequences to detect members of the Paramyxovirinae or Pneumovirinae subfamily or groups of genera within the Paramyxovirinae subfamily. The consensus-degenerate hybrid oligonucleotide primer design and seminested or nested PCR assay design were used to enhance the breadth of reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
262
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(278 citation statements)
references
References 17 publications
1
262
0
3
Order By: Relevance
“…Cultures displaying syncytial CPE were screened using subfamily-or genus-specific primer sets following protocols described elsewhere (Tong et al, 2008). PCR products were sequenced directly for preliminary characterization of the viral genomic sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures displaying syncytial CPE were screened using subfamily-or genus-specific primer sets following protocols described elsewhere (Tong et al, 2008). PCR products were sequenced directly for preliminary characterization of the viral genomic sequences.…”
mentioning
confidence: 99%
“…MenPV was isolated from the 2009 Cedar Grove collection and reported previously . MenPV is another known bat rubulavirus, closely related to TioPV, and was found to be the aetiological agent of a disease in pigs in Phylogenetic analysis based on the 530 bp fragment of the large (L) gene obtained using pan-Paramyxovirinae primers (Tong et al, 2008), which is the most used sequence for paramyxovirus phylogeny studies (Drexler et al, 2012), indicated that three of the four newly isolated bat rubulaviruses clustered with the two previously identified Asian bat viruses, MenPV and TioPV. However, the fourth newly isolated virus, HerPV, was more closely related to the Achimota virus 2 isolated from bats in Ghana, Africa (Fig.…”
mentioning
confidence: 99%
“…Both degenerate 293 and non-degenerate primers for the PCR detection of reoviruses and paramyxoviruses failed to 294 identify this new virus. Of particular note, we were unable to detect Sunshine virus using the primer 295 sets published by Tong et al (2008). One of these primer sets (PAR-F1, PAR-F2 and PAR-R) was 296 designed to detect all the members of the subfamily Paramyxovirinae while another set (PNE-F1, 297 PNE-F2 and PNE-R) was designed to detect all the members of the subfamily Pneumovirinae.…”
mentioning
confidence: 97%
“…Samples were tested by the panel of panparamyxovirus RT-PCR assays using a commercial 1-step RT-PCR kit. 22 13 buffer with a final concentration of 2.0 mM MgSO 4 , 20 units of RNase inhibitor, a 5-ml aliquot of RNA extracts, and 1 unit of an RT-Taq mix. c Water was added to achieve a final volume of 50 ml.…”
mentioning
confidence: 99%
“…22 This group of paramyxovirus PCR primers collectively target highly conserved amino acid sequences within each of 2 subfamilies and each of 2 genera subgroups, based on the multiple alignments of 33 deduced, nonredundant paramyxovirus L polymerase genes. This broadly reactive RT-PCR, coupled with sequence analysis and IHC, identified CDV in this canine case of MUE.…”
mentioning
confidence: 99%